The Advantages and Cultivation of Medicinal Plants as a Living Dispensary in Sukajadi Village - Purwanti, Yani; Ardiyanti, Vivit; Kriswantoro, Haris; Zairani, Fitri Yetty; Nisfuriah, Laili (Universitas Muhammadiyah Palembang, 2022)
Indonesia is known as one country with a high diversity of flora. Several plants that grow in Indonesia produce certain compounds as medicines and as the primary raw materials in the pharmaceutical industry. The wealth of natural resources owned should be known by the people of Indonesia and can use them to improve welfare, including maintaining their health. The people of Sukajadi Village, Sungai Rattan District, and Muara Enim Regency need to be informed about the types, benefits, and methods of cultivating medicinal plants and making Live Pharmacies. This knowledge is advantageous to help rural communities overcome health problems with mild symptoms because, during the COVID-19 PANDEMIC, which has been going on for a long time, it turns out to cause concern. People fear contracting the COVID-19 virus, which is very dangerous if they go to hospitals, PUSKESMAS and other health facilities. Knowledge of the types, benefits and availability of live dispensaries in each residential area is expected to help rural communities overcome diseases with only mild symptoms and must continue to seek medical treatment. Medicinal plants are felt to have not been able to overcome the disease, especially for people with serious illnesses.